Early postoperative outcomes and complications of laparoscopic versus open ventral/incisional hernia repair: a meta-analysis - Chinnappa, Arjun; Srikanth, Sudarsan (International Surgery Journal, 2025)
Laparoscopic repair has been increasingly utilized for ventral/incisional hernias, but its impact on early postoperative outcomes remains debated. We conducted a meta-analysis comparing early complications and recovery after laparoscopic versus open ventral hernia repair. A systematic literature search was performed using Medline, Embase, and Cochrane databases to identify studies comparing laparoscopic and open ventral/incisional hernia repair. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated for postoperative outcomes using random-effects models. Fourteen randomized controlled trials and observational studies encompassing 1,340 patients were included. Operative duration was longer for laparoscopic repair (pooled weighted mean difference 25.1 min, 95% CI 15.8-34.4 min), but length of stay was shorter (pooled weighted mean difference -1.52 days, 95% CI -2.04 to -1.00 days). Pain scores favoured the laparoscopic technique at 24 hours (pooled mean difference -1.54 units, 95% CI -2.09 to -0.99 units) and 1 week (pooled mean difference -1.74 units, 95% CI -2.67 to -0.81 units). Laparoscopic repair had lower risks of overall complications (OR 0.49, 95% CI 0.33-0.71) and surgical site occurrences (OR 0.22, 95% CI 0.12-0.40). The risks of mesh infection and bowel obstruction were similar between groups. Laparoscopic ventral hernia repair results in shorter hospital stays, less pain, faster recovery and fewer wound complications compared to open repair. These findings support the use of a minimally invasive approach. Technical training is necessary to avoid increased operative times.